1987
DOI: 10.1002/hlca.19870700413
|View full text |Cite
|
Sign up to set email alerts
|

Some Cyclic Oligopeptide with S2n Symmetry

Abstract: Some cyclic oligopeptides formed by an equal number of alternating D‐ and L‐amino‐acid residues have been synthesized by using the hydrochloride of the open‐chain peptide acid as precursor and the mixed‐anhydride condensation method. The cyclic oligopeptides (tetra‐, hexa‐, and octavaline, hexaleucine, and hexaphenylalanine) form very stable H‐bonded structures (IR‐amide band at 3270–3290 cm−1) which are insoluble in common organic solvents. In CF3COOH/CDCI3 (25°), they yield 1H‐NMR spectra snowing the expecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
25
0
2

Year Published

1998
1998
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(27 citation statements)
references
References 8 publications
0
25
0
2
Order By: Relevance
“…[79±82] Initial attempts to experimentally demonstrate this type of tubular construct proved inconclusive. [83] In 1989 an X-ray crystallographic study by Lorenzi and co-workers on the hexapeptides cyclo-[-(l-Phe-d-Phe) 3 -] and cyclo[-(l-Val-d-Val) 3 -] revealed that the expected intersubunit associations were absent and each peptide was found instead to be tightly hydrogen bonded to several cocrystallized solvent molecules. [84] In 1993 our laboratory compellingly demonstrated the formation of hollow tubular structures by the stacking of cyclic d,l-peptide rings (Scheme 1).…”
Section: Helical Folding Of Linear Oligophenylacetylenesmentioning
confidence: 99%
“…[79±82] Initial attempts to experimentally demonstrate this type of tubular construct proved inconclusive. [83] In 1989 an X-ray crystallographic study by Lorenzi and co-workers on the hexapeptides cyclo-[-(l-Phe-d-Phe) 3 -] and cyclo[-(l-Val-d-Val) 3 -] revealed that the expected intersubunit associations were absent and each peptide was found instead to be tightly hydrogen bonded to several cocrystallized solvent molecules. [84] In 1993 our laboratory compellingly demonstrated the formation of hollow tubular structures by the stacking of cyclic d,l-peptide rings (Scheme 1).…”
Section: Helical Folding Of Linear Oligophenylacetylenesmentioning
confidence: 99%
“…Additionally, the staggered nanotube structure of (+)- 3 forms an infinite array in the crystal lattice (four molecules/unit cell as illustrated in Figure 4b–d). Given the pyrrolinone scaffold comprises a designed peptidomimetic, our work has obvious parallels to the cyclic peptides pioneered by Karle,15 Lorenzi,16 and Ghadiri 17,9. Of particular interest, the 1987 report by G. P. Lorenzi et al discloses a series of D,L-alternating cyclic hexapeptides 16.…”
mentioning
confidence: 94%
“…Given the pyrrolinone scaffold comprises a designed peptidomimetic, our work has obvious parallels to the cyclic peptides pioneered by Karle,15 Lorenzi,16 and Ghadiri 17,9. Of particular interest, the 1987 report by G. P. Lorenzi et al discloses a series of D,L-alternating cyclic hexapeptides 16. In contrast to the hexapeptides, which were reported to be completely insoluble in all common organic solvents, (+)- 2 and (+)- 3 are moderately soluble in most polar organic solvents (i.e., EtOAc, EtOH), and display excellent solubility in CHCl 3 .…”
mentioning
confidence: 94%
“…For example, macrocycles with an orthogonal arrangement (orthogonal substituents, Figure 2, left) of polar functional groups are able to form tubular superstructures in the solid state. [5] If the polar functional groups point to the outside of the macrocycle (extraannular substituents, Figure 2, middle) this may lead to the formation of a 2D network in the solid state. [6] Shape-persistent macrocycles with polar groups pointing to the inside (intraannular substituents, Figure 2, right) play a special role in supramolecular chemistry.…”
Section: Introductionmentioning
confidence: 99%